LipL41, a hemin binding protein from Leptospira santarosai serovar Shermani. - Ming-Hsing Lin (Public Library of Science (PLoS), 2013)
Leptospirosis is one of the most widespread zoonotic diseases in the world. It is caused by the pathogen Leptospira that results in multiple-organ failure, in particular of the kidney. Outer membrane lipoprotein is the suspected virulence factor of Leptospira. In Leptospira spp LipL41 is one major lipoprotein and is highly conserved. Previous study suggests that LipL41 bears hemin-binding ability and might play a possible role in iron regulation and storage. However, the characterization of hemin-binding ability of LipL41 is still unclear. Here the hemin-binding ability of LipL41 was examined, yielding a K d = 0.59 ± 0.14 μM. Two possible heme regulatory motifs (HRMs), C[P/S], were found in LipL41 at (140)Cys-Ser and (220)Cys-Pro. The mutation study indicates that Cys140 and Cys220 might be cooperatively involved in hemin binding. A supramolecular assembly of LipL41 was determined by transmission electron microscopy. The LipL41 oligomer consists of 36 molecules and folds as a double-layered particle. At the C-terminus of LipL41, there are two tetratricopeptide repeats (TPRs), which might be involved in the protein-protein interaction of the supramolecular assembly.